Corrosion-resistant and flame-retardant cross-linked polyolefin cable

Through the multi-layer structure and specific materials combination of crosslinked polyolefin cables, the corrosion and aging problems of high-voltage DC cables in high temperature and harsh environments are solved, efficient electromagnetic shielding, fire resistance and flame retardant, extending the service life of the cables and Improved performance.

CN119181532AActive Publication Date: 2024-12-24ZHONGXIANG OPTOELECTRONIC TECH CO LTD

Patent Information

Application Number
CN202411224527.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-24
Estimated Expiration
2044-09-03

AI Technical Summary

Technical Problem

Existing high-voltage DC cables are prone to corrosion and aging in high temperature and harsh environments, resulting in material breakdown and short circuit, making it difficult to meet the performance requirements of high voltage resistance, electrical insulation, flame retardant, anti-interference, high and low temperature resistance and long service life.

Method used

Using cross-linked polyolefin cable structure, including cable core, tape wrapping layer, inner shielding layer, flame retardant layer, outer shielding layer, outer shielding layer and protective coating, ceramic flame retardant polyolefin composite materials and ferrite-containing The polyolefin composite shielding material and halogen-free low smoke flame-retardant corrosion-resistant polyolefin mixture combine with aluminum foil mela belt and polyurethane aqueous coating to form a double-layer electromagnetic shielding and double-layer protection.

Benefits of technology

It realizes excellent mechanical properties, high voltage resistance, tensile resistance, bending resistance, water resistance, corrosion resistance, interference resistance, radiation resistance and high and low temperature stability of the cable, and the combustion performance reaches halogen-free, low smoke flame retardant Class A, grade It can reach level B1, extending the service life of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181532A_ABST
    Figure CN119181532A_ABST
Patent Text Reader

Abstract

The invention discloses a corrosion-resistant and flame-retardant cross-linked polyolefin cable, and belongs to the technical field of polyolefin cable manufacturing. The corrosion-resistant and flame-retardant cross-linked polyolefin cable comprises a conductor wrapped with an isolating layer, an oxygen isolating layer and an insulating layer are sequentially extruded outside the isolating layer, then a belting layer is wrapped outside the isolating layer, and then a polyolefin composite shielding material inner shielding layer containing ferrite and a ceramic flame-retardant polyolefin composite material flame-retardant layer are sequentially extruded outside the isolating layer. An aluminum foil Mylar tape is lapped to form an outer shielding layer, finally, a halogen-free low-smoke flame-retardant corrosion-resistant polyolefin mixture outer protection layer is coated, and a protective coating is coated. The corrosion-resistant and flame-retardant cross-linked polyolefin cable is simple in structure and easy to manufacture, has excellent mechanical properties, high pressure resistance, tensile resistance, bending resistance, flame retardance, waterproofness, corrosion resistance, aging resistance, interference resistance, radiation resistance and high and low temperature impact resistance, and prolongs the high-temperature service life of the cable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyolefin cable manufacturing, and in particular relates to a corrosion-resistant and flame-retardant cross-linked polyolefin cable and a manufacturing method thereof. Background Art

[0002] With the acceleration of urbanization and industrialization in my country, high-voltage, ultra-high-voltage and ultra-high-voltage transmission with advantages such as long distance and large capacity has developed rapidly. High-voltage direct current transmission has the characteristics of low loss, long distance, large capacity, convenient power connection and control, and simple adjustment. Therefore, high-voltage direct current cables need to have good electrical insulation, corrosion resistance, flame retardancy, voltage resistance, low dielectric loss, light weight, high and low temperature stability, aging resistance and mechanical properties.

[0003] At present, the main problems encountered by high-voltage DC cable insulation materials are the conductivity temperature characteristics and space charge accumulation problems. The gap between the conductor and the insulation layer easily causes the space charge to accumulate, causing material aging and cracking, and ultimately leading to material breakdown; the operating temperature of the high-voltage cable is relatively high, and the real-time temperature in an unstable state can exceed 110°C, which accelerates the aging of the insulation layer and causes breakdown. Therefore, the high-voltage DC cable requires better high-temperature stability and flame retardancy; most high-voltage DC cables have harsh working environments, such as mines, deep seas, aerospace, nuclear power and other environments. Long-term use is prone to environmental corrosion or harm, which can easily cause short-circuit damage to the high-voltage cable, affect the normal use of the cable, and shorten the service life of the cable. In the fields of nuclear power plants, marine communications, electronic communications, railway transportation, aerospace transportation, etc., at this stage, domestic high-voltage cables generally cannot meet the performance of high voltage resistance, electrical insulation, high flame retardancy, corrosion resistance, anti-interference, high and low temperature resistance, aging resistance, and long service life at the same time. This is also a problem that the technical personnel of the present invention strive to solve, in order to reach the technical level of foreign countries and break the technical monopoly of foreign enterprises.

[0004] Invention patent CN201911309331.2 discloses an anti-interference, highly flame-retardant and environmentally friendly transponder data transmission cable, which uses a double composite high electromagnetic shielding layer to form a three-level shielding, has strong anti-interference ability and minimizes the amount of smoke and toxic gases generated by combustion. However, the insulation layer of this patent uses high-temperature resistant fluoroplastics, which does not belong to the development trend of halogen-free cables; the semiconductor nylon tape wrapped around the cable core is prone to static electricity accumulation during long-term operation, which affects the insulation of the cable, and the elongation performance is general. In a low temperature environment, it is easy to crack, which affects the quality and service life of the high-voltage cable. Invention patent CN201911116173.9 discloses a high-voltage soft polyolefin wire material for new energy vehicles, which uses elastomeric rubber, elastomeric polyethylene, olefin copolymers and other raw materials to prepare by radiation cross-linking, and has the characteristics of good comprehensive performance, good flame retardancy and high temperature resistance, and sufficient toughness, but the corrosion resistance of the polyolefin material is not good, and it is not mentioned in the scheme. Invention patent CN202311194403.X discloses a medium- and high-voltage cable for smart grid, including a cable core, an insulating inner layer and a protective outer layer, wherein the protective outer layer is made of PVC, chloroprene rubber, and ethylene-vinyl acetate copolymer as the main raw materials, and has high surface strength, waterproofness, wear resistance, flame retardancy and corrosion resistance. However, the protective outer layer of the high-voltage cable contains PVC, which does not conform to the current development trend of halogen-free cables. At the same time, the cable does not contain a shielding layer, so the cable does not have anti-interference, radiation resistance and other properties, which limits its scope of use. Summary of the invention

[0005] The main purpose of the present invention is to provide a corrosion-resistant and flame-retardant cross-linked polyolefin cable, which has a simple structure, is easy to manufacture, and has excellent mechanical properties, high pressure resistance, tensile and bending resistance, waterproofness, corrosion resistance, aging resistance, anti-interference, radiation resistance and high and low temperature impact resistance. At the same time, the combustion performance of the polyolefin cable is halogen-free low-smoke flame-retardant Class A, and the grade can reach Class B. 1 The invention can withstand temperatures as low as -40°C, ensuring that the high-voltage cable of the invention has a better use effect and a longer service life in harsh environments.

[0006] In order to achieve the purpose of the present invention, the present invention provides a corrosion-resistant and flame-retardant cross-linked polyolefin cable, comprising a cable core, a tape layer, an inner shielding layer, a flame-retardant layer, an outer shielding layer, an outer sheath and a protective coating, wherein the cable core is one or more wire cores, and the wire core comprises a conductor, an isolation layer, an insulating layer and an oxygen-isolating layer, the conductor is wrapped with an isolation layer, the isolation layer is extruded with an oxygen-isolating layer, and the oxygen-isolating layer is extruded with an insulating layer;

[0007] The insulating layer is wrapped with a tape layer, the tape layer is extruded with an inner shielding layer, the inner shielding layer is extruded with a flame retardant layer, the flame retardant layer is wrapped with an aluminum foil Mylar tape as an outer shielding layer, the outer shielding layer is covered with an outer protective layer, and the outer protective layer is coated with a protective coating;

[0008] The inner shielding layer is a polyolefin composite shielding material containing ferrite;

[0009] The flame retardant layer is a ceramic flame retardant polyolefin composite material;

[0010] The outer protective layer is a halogen-free, low-smoke, flame-retardant, and corrosion-resistant polyolefin mixture.

[0011] Furthermore, when the cable core is composed of one wire core, the wrapping tape layer is directly wrapped around the outside of the insulation layer; when the cable core is composed of two or more wire cores, the multiple wire cores are twisted to form the cable core, and then the filling rope is filled in the gap between the cable cores, and then the wrapping tape layer is wrapped.

[0012] Furthermore, the polyolefin composite shielding material is composed of the following raw materials in parts by mass: 40-60 parts of polypropylene resin, 25-35 parts of ethylene-vinyl acetate copolymer, 15-25 parts of ethylene-butyl acrylate copolymer, 5-10 parts of PP grafted maleic anhydride, 5-15 parts of carbon black, 3-6 parts of barium ferrite, 10-20 parts of flame retardant, 0.1-0.5 parts of initiator DCP, 0.5-2 parts of first silane coupling agent, 0.3-0.5 parts of antioxidant, and 1-3 parts of lubricant.

[0013] Furthermore, the preparation method of the barium ferrite is:

[0014] S1. Add appropriate proportions of ferrous nitrate, ferric nitrate and polyethylene glycol to an appropriate amount of deionized water and stir continuously until dissolved, then add ammonia water to adjust the pH value to 10-11, heat to 50-70 ° C for 2-4h, filter, wash and dry to obtain an iron oxide precursor;

[0015] S2. The iron oxide precursor and barium carbonate prepared above are added to glacial acetic acid and stirred until dissolved to form a mixed solution;

[0016] S3. Add an appropriate amount of dilute nitric acid to the mixed solution, stir for 5-10 minutes, then heat to 200-220°C to react for 3-5 hours, cool to room temperature, filter, and then wash with deionized water and anhydrous ethanol 2-3 times in succession, and vacuum dry at 80°C for 2-5 hours to obtain barium ferrite.

[0017] Furthermore, the molar ratio of ferrous nitrate to ferric nitrate is (0.4-0.6):1;

[0018] The molar ratio of iron to barium carbonate in the iron oxide precursor is (9-10):1.

[0019] Furthermore, the flame retardant is composed of microencapsulated red phosphorus and organic montmorillonite in a ratio of 1:4 by mass.

[0020] Furthermore, the ceramic flame-retardant polyolefin composite material is composed of the following raw materials in parts by mass: 30-50 parts of low-density polyethylene, 15-30 parts of ethylene-methyl acrylate copolymer, 25-40 parts of ethylene propylene diene terpolymer, 30-50 parts of aminosilane-coated wollastonite, 10-20 parts of low-melting point glass powder, 15-25 parts of phlogopite powder, 5-10 parts of lithium borate salt, 6-12 parts of halogen-free flame retardant, 0.2-0.4 parts of initiator DCP and 1-3 parts of a second silane coupling agent.

[0021] Furthermore, the aminosilane-coated wollastonite uses aminopropyltriethoxysilane to perform surface modification on the wollastonite, and the coating rate is ≥70%;

[0022] The lithium borate salt is composed of lithium tetraborate, lithium metaborate and zinc borate in a mass ratio of 1:2:4;

[0023] The halogen-free flame retardant is composed of nano magnesium hydroxide, magnesium stearate and silicone oil in a mass ratio of (0.2-0.5):1:1;

[0024] The second silane coupling agent is composed of vinyltrimethoxysilane and aminopropyltriethoxysilane.

[0025] Furthermore, the halogen-free, low-smoke, flame-retardant, and corrosion-resistant polyolefin mixture is composed of the following raw materials in parts by mass: 30-50 parts of linear low-density polyethylene, 10-15 parts of ultra-high molecular weight polyethylene, 30-50 parts of ethylene-ethyl acrylate copolymer, 15-30 parts of metallocene ethylene-octene copolymer, 15-30 parts of methyl vinyl silicone rubber, 20-40 parts of low-melting point glass powder, 15-25 parts of plasticizer, 30-50 parts of composite flame retardant, 10-15 parts of titanium aluminum oxide, 20-40 parts of filler, 0.3-0.5 parts of antioxidant, 0.2-0.4 parts of initiator DCP, and 3-5 parts of a third silane coupling agent.

[0026] Furthermore, the composite flame retardant is composed of the following raw materials in parts by mass: 40-60 parts of nano magnesium hydroxide, 30-40 parts of aluminum hydroxide and 10-20 parts of zinc borate.

[0027] Furthermore, the titanium aluminum oxide is a mixture of titanium dioxide and aluminum oxide in a mass ratio of 3:2;

[0028] The filler is composed of calcined kaolin, phlogopite powder and calcium carbonate in a mass ratio of 1:2:1;

[0029] The third silane coupling agent is vinyltrimethoxysilane.

[0030] Furthermore, the isolation layer is a halogen-free and corrosion-free non-woven fabric of polyester fiber or terylene fiber;

[0031] The insulating layer is made of 150°C irradiation cross-linked flame-retardant polyolefin insulating material;

[0032] The oxygen barrier layer is a low-smoke, halogen-free, flame-retardant cable material with an oxygen index greater than or equal to 40;

[0033] The wrapping tape layer is a halogen-free, low-smoke, high-flame-retardant tape made of non-woven fabric or glass fiber cloth, which is wrapped around the insulation layer in an overlapping manner with an overlap rate of 15-20%;

[0034] The outer shielding layer is an aluminum foil Mylar tape;

[0035] The protective coating is a flame retardant and corrosion resistant polyurethane water-based coating.

[0036] The present invention has achieved the following beneficial effects:

[0037] 1. The present invention adopts a halogen-free, low-smoke, flame-retardant, and corrosion-resistant polyolefin mixture as the outer sheath, and uses a composite polyolefin (i.e., linear low-density polyethylene, ultra-high molecular weight polyethylene, ethylene-ethyl acrylate copolymer, and metallocene ethylene-octene copolymer) as a matrix, which ensures that the present invention has excellent electrical insulation, mechanical strength, and bending tensile properties, and at the same time has excellent comprehensive properties such as corrosion resistance, waterproofness, wear resistance, and low temperature resistance; the addition of methyl vinyl silicone rubber has good compatibility with polyolefin resin, and significantly improves the corrosion resistance, flame retardancy, electrical insulation, aging resistance, high temperature resistance, and waterproofness of the outer sheath, and further improves the high-temperature service life of the cable; the addition of titanium aluminum oxide significantly improves the high temperature resistance and flame retardancy of the cable, so that the present invention has better mechanical strength, wear resistance, corrosion resistance, radiation resistance, etc.

[0038] 2. The present invention adopts ceramic flame-retardant polyolefin composite material as the flame-retardant layer, which not only improves the flame retardancy of the polyolefin cable, but also improves the mechanical strength, tensile strength, bending resistance, wear resistance and corrosion resistance of the cable, and can effectively play a role in fire retardancy and anti-aging.

[0039] 3. The present invention uses a polyolefin composite shielding material containing ferrite as the inner shielding layer, which improves the electromagnetic shielding performance of the cable, and also plays a role in radiation resistance, and also reduces the resistivity and cost, thereby extending the service life of the polyolefin cable. At the same time, the inner shielding layer of the polyolefin composite shielding material containing ferrite and the outer shielding layer of aluminum foil Mylar tape constitute a double-layer electromagnetic shielding, which reduces the signal interference and space charge accumulation problems of the polyolefin cable, and at the same time improves the radiation resistance, high temperature resistance and flame retardancy of the cable.

[0040] 4. The present invention sprays a protective coating on the outer sheath, which can effectively provide fire retardant, anti-aging, wear-resistant and other properties, thereby improving the overall outer layer protection capability of the cable and extending its service life.

[0041] 5. The base materials of the insulating layer, oxygen barrier layer, flame retardant layer and outer sheath of the present invention are all polyolefin, halogen-free and environmentally friendly, ensuring that the polyolefin cable still has excellent mechanical strength, electrical insulation, tensile and bending resistance, waterproofness, corrosion resistance, aging resistance and high and low temperature stability under high voltage conditions, and has a long service life; the combustion performance of the polyolefin cable is halogen-free low-smoke flame retardant Class A, and the grade can reach B 1 class.

[0042] 6. The corrosion-resistant and flame-retardant cross-linked polyolefin cable prepared by the present invention has a smooth surface, a simple structure, is easy to manufacture, has excellent flame-retardant and corrosion-resistant properties, a wide range of applications, and is low in cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 It is a structural schematic diagram of a single-core cable of the corrosion-resistant and flame-retardant cross-linked polyolefin cable of the present invention;

[0044] Figure 2 It is a schematic structural diagram of a three-core cable of the corrosion-resistant and flame-retardant cross-linked polyolefin cable of the present invention.

[0045] Figure symbols: 1. Conductor; 2. Isolation layer; 3. Oxygen barrier layer; 4. Insulation layer; 5. Tape layer; 6. Inner shielding layer; 7. Flame retardant layer; 8. Outer shielding layer; 9. Outer sheath; 10. Protective coating; 11. Filling rope. DETAILED DESCRIPTION

[0046] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] like Figure 1 As shown, the present invention provides a corrosion-resistant and flame-retardant cross-linked polyolefin cable, comprising a cable core, a tape layer 5, an inner shielding layer 6, a flame-retardant layer 7, an outer shielding layer 8, an outer sheath 9 and a protective coating 10, wherein the cable core is one or more wire cores, and the wire core comprises a conductor 1, an isolation layer 2, an insulating layer 4 and an oxygen barrier layer 3.

[0048] When the cable core is a wire core (such as Figure 1As shown in the figure, the conductor 1 is wrapped with an isolation layer 2, the isolation layer 2 is extruded with an oxygen barrier layer 3, the oxygen barrier layer 3 is extruded with an insulation layer 4, the insulation layer 4 is wrapped with a tape layer 5, the tape layer 5 is extruded with an inner shielding layer 6, the inner shielding layer 6 is extruded with a flame retardant layer 7, the flame retardant layer 7 is wrapped with an aluminum foil Mylar tape as an outer shielding layer 8, the outer shielding layer 8 is covered with an outer sheath 9, and the outer sheath 9 is coated with a protective coating 10. The embodiment of the present invention mainly describes a single-core cross-linked polyolefin cable.

[0049] When the cable core is composed of two or more wire cores (such as Figure 2 As shown, when there are 3 cores), the 3 cores are twisted to form a cable core, and then the filling rope 11 is filled in the gap between the cable cores, and then the wrapping tape layer 5 is wrapped around it.

[0050] Preferably, the isolation layer 2 is a halogen-free and non-corrosive non-woven fabric such as polyester fiber and polyester fiber. The isolation layer 2 is provided to protect the electrical properties of the conductor 1 of the present invention, to be waterproof and fireproof, and to effectively prevent the conductor 1 from corrosion, aging or short circuit, and to facilitate the stripping of the insulating layer 4 from the conductor 1 during installation, while having good insulation and flame retardant properties. In the embodiment of the present invention, the isolation layer 2 is made of polyester halogen-free and non-corrosive non-woven fabric (Jiangsu Yilong Textile), with a thickness of 0.1-0.3 mm.

[0051] Preferably, the oxygen barrier layer 3 is a low-smoke halogen-free flame-retardant cable material with an oxygen index greater than or equal to 40. The oxygen barrier layer 3 is used to protect the isolation layer 2, delay the ignition time of the conductor 1 in the event of a fire, reduce losses, and ensure that the present invention has good insulation and electrical properties. In the embodiment of the present invention, the low-smoke halogen-free flame-retardant cable material is selected from EPC6909 of Yangzhong Oubao Chemical.

[0052] Preferably, the insulating layer 4 is a 150°C irradiation cross-linked flame-retardant polyolefin insulation material, which is halogen-free and environmentally friendly, and can effectively protect the electrical properties of the conductor 1, ensuring that the polyolefin cable has excellent insulation and flame retardancy, and improving the mechanical properties, aging resistance, corrosion resistance and temperature resistance of the cable. In the embodiment of the present invention, the 150°C irradiation cross-linked flame-retardant polyolefin insulation material is selected from the production of CGN High-Tech Nuclear Materials.

[0053] Preferably, the tape layer 5 is a halogen-free, low-smoke, high-flame-retardant tape made of non-woven fabric or glass fiber cloth, which is overlapped and wrapped outside the insulating layer 4, with an overlap rate of 15-20%. In order to further ensure that the product reaches the halogen-free, low-smoke, flame-retardant Class A specified in the national standard, and the combustion performance level reaches the national standard B1 level, the preferred tape layer 5 in the embodiment of the present invention uses the halogen-free, low-smoke, high-flame-retardant glass fiber tape of Shuangxiong Cable, which has a thickness of 0.2mm and can withstand a temperature of 300°C. It adopts double-layer overlapping wrapping and an overlap rate of 20%. Using the halogen-free, low-smoke, high-flame-retardant glass fiber tape of the present invention as the tape layer 5 not only improves the flame retardant effect of the cable of the present invention, but also improves the high and low temperature resistance, chemical corrosion resistance, insulation and anti-static properties of the present invention, further ensuring the insulation and service life of the cable of the present invention.

[0054] Preferably, the inner shielding layer 6 is a polyolefin composite shielding material containing ferrite, which can significantly improve the anti-interference and radiation resistance of the cable of the present invention, and reduce the resistivity and cost, ensure that the surface of the inner shielding layer 6 is smooth, and further prevent the electric field distortion from damaging the insulating layer 4, thereby extending the service life of the cable of the present invention.

[0055] The polyolefin composite shielding material is composed of the following raw materials in parts by weight: 40-60 parts of polypropylene resin, 25-35 parts of ethylene-vinyl acetate copolymer, 15-25 parts of ethylene-butyl acrylic acid copolymer, 5-10 parts of PP grafted maleic anhydride, 5-15 parts of carbon black, 3-6 parts of barium ferrite, 10-20 parts of flame retardant, 0.1-0.5 parts of initiator DCP, 0.5-2 parts of first silane coupling agent, 0.3-0.5 parts of antioxidant, and 1-3 parts of lubricant. The raw material combination and proportion of the polyolefin composite shielding material ensure that the present invention has good anti-interference, mechanical properties and combustion performance, and interacts with each component of the cable to ensure that it has excellent comprehensive performance.

[0056] Polypropylene resin (selected from Korean Lotte's polypropylene JI-320), ethylene-vinyl acetate copolymer (selected from Japan Mitsui's EVA 45X) and ethylene-butyl acrylic acid copolymer (selected from Dow's EBA 3217) are selected and combined in appropriate proportions to ensure that the polyolefin composite shielding material has easy processing, better mechanical properties and ductility, and improves the crosslinking density and temperature resistance level. PP grafted maleic anhydride (selected from SK Chemical's The addition of carbon black improves the compatibility between PP and other components, making the components closely bonded, thereby improving the mechanical properties and tensile and bending properties of the inner shielding layer 6. The use of carbon black (acetylene carbon black selected from Tianjin Huacai Chemical) improves the conductivity of the polyolefin composite shielding material and reduces the cost; however, if the amount of carbon black added is too much, the inner shielding layer 6 prepared is brittle, has poor ductility, low elongation at break, and affects the smoothness of the surface of the inner shielding layer 6, thereby affecting the mechanical properties and flexibility of the cable, and easily causing electric field distortion to damage the insulating layer 4, reducing the service life of the cable; if the amount of carbon black is too little, the conductivity of the inner shielding layer 6 cannot be guaranteed, reducing the anti-interference performance of the cable, etc.

[0057] The present invention uses carbon black and barium ferrite in appropriate proportions, which not only improves the conductivity of the inner shielding layer 6, but also improves the high temperature resistance and wear resistance of the cable of the present invention, so that the cable has better anti-interference, radiation resistance and corrosion resistance, but also ensures that the inner shielding layer 6 has excellent mechanical strength, flexibility, and surface smoothness, thereby extending the high temperature service life of the cable.

[0058] Preferably, barium ferrite BaFe 12 O 19 Commercially available or homemade ones can be selected, wherein the commercially available barium ferrite is selected from Wuhan Langbowan Biomedicine Company.

[0059] Homemade barium ferrite BaFe 12 O 19 The specific preparation process is:

[0060] S1. Add 371.8 g of ferrous nitrate, 1 kg of ferric nitrate (i.e., the molar ratio of ferrous nitrate to ferric nitrate is 1:2) and 96 g of PEG8000 into 1.2 L of deionized water and stir continuously until dissolved, then add ammonia water to adjust the pH value to 11, heat to 60 ° C for 4 h, filter, wash and dry to obtain an iron oxide precursor;

[0061] S2. The iron oxide precursor prepared above and 122.4 g of barium carbonate (ie, the molar ratio of iron to barium carbonate in the iron oxide precursor is 10:1) are added to 1 L of glacial acetic acid and stirred until dissolved to form a mixed solution;

[0062] S3. Add 700 mL of 4 mol / L dilute nitric acid to the above mixed solution, stir for 10 min, then heat to 220 °C to react for 4 h, cool to room temperature, filter, then wash with deionized water and anhydrous ethanol three times in succession, and vacuum dry at 80 °C for 3 h to obtain barium ferrite.

[0063] The barium ferrite BaFe prepared by the present invention 12 O 19The preparation method is easy to operate, and the barium ferrite obtained has small grain size, good dispersibility, and few impurities, which can significantly improve the conductivity and anti-interference properties of the inner shielding layer 6, and can also significantly improve the radiation resistance and corrosion resistance of the present invention, and ensure that the mechanical strength, flexibility, surface smoothness, etc. of the inner shielding layer 6 meet the cable requirements.

[0064] Preferably, the flame retardant is composed of microencapsulated red phosphorus (selected from Yimin Chemical's 2000 mesh coated red phosphorus flame retardant YMRP-90) and organic montmorillonite (selected from Longchuan's nano-montmorillonite) in a mass ratio of 1:4. The flame retardant combination has good compatibility with components such as polyolefins, can significantly improve the flame retardancy, corrosion resistance and wear resistance of the present invention, and ensure that the present invention has good mechanical properties and electrical properties.

[0065] Preferably, the first silane coupling agent is vinyltrimethoxysilane, which, on the one hand, is to improve the bonding force between the organic and inorganic components in the polyolefin composite shielding material, thereby improving the mechanical strength of the inner shielding layer 6; on the other hand, it increases the crosslinking density between polyolefin resins, further improving the mechanical properties, water resistance and high temperature resistance of the polyolefin composite shielding material.

[0066] Preferably, the antioxidant is antioxidant 1010, which improves the heat-oxidative aging resistance of the polyolefin composite shielding material, is not easy to migrate, and has high thermal stability. The lubricant is CYD-P214, which improves the processing fluidity and dimensional stability of the polyolefin composite shielding material.

[0067] Preferably, the flame retardant layer 7 is a ceramic flame retardant polyolefin composite material, which has high mechanical strength and chemical stability, can be used for a long time at 150°C, and can form a ceramic body during the combustion process in the flame, which significantly improves the fire retardancy, smoke suppression and thermal insulation properties, and the oxygen index is ≥35. It also has a supporting function, improves the wear resistance and corrosion resistance of the cable, and has good thermal shock resistance and electrical properties.

[0068] The ceramic flame-retardant polyolefin composite material is composed of the following raw materials in parts by mass: 30-50 parts of low-density polyethylene, 15-30 parts of ethylene-methyl acrylate copolymer, 40-60 parts of ethylene-propylene diene terpolymer, 30-50 parts of aminosilane-coated wollastonite, 10-20 parts of low-melting-point glass powder, 15-25 parts of phlogopite powder, 5-10 parts of lithium borate salt, 0.2-0.4 parts of initiator DCP, 6-12 parts of halogen-free flame retardant and 1-3 parts of a second silane coupling agent.

[0069] In order to ensure that the present invention has excellent mechanical properties, combustion performance and non-corrosiveness, the present invention preferably has a low-density polyethylene melt index of 1.5-4g / 10min at 190°C and 2.16Kg load (Shanghai Petrochemical's DJ210 is selected in the present embodiment); an ethylene-methyl acrylate copolymer melt index of 5-10g / 10min at 190°C and 2.16Kg load (Arkema's LOTADER AX8900 is selected in the present embodiment); an ethylene content of 40-55wt% and a propylene content of 40-50wt% in the ethylene-propylene diene terpolymer (Dow's EPDM565 is selected in the present embodiment). The performance settings and combination of low-density polyethylene, ethylene-methyl acrylate copolymer and EPDM can enable the present invention to burn for 20min under a fire source with a power of 20.5kW without any dripping during the period; the present invention burns at 935°C with a conductivity of ≤10μs / mm and a pH of ≥4.

[0070] Aminosilane coated wollastonite, low melting point glass powder and phlogopite powder are added as ceramic fillers of the ceramic material, which not only has good bonding strength with the polyolefin material, but also improves the mechanical strength, electrical insulation, high temperature resistance and corrosion resistance of the cable of the present invention.

[0071] The addition of low-melting-point glass powder improves the mechanical strength, corrosion resistance, wear resistance, high temperature resistance and combustion performance of the ceramic flame-retardant polyolefin composite material, and further ensures that the cable of the present invention meets the requirements of halogen-free low-smoke flame-retardant Class A, and the combustion performance level reaches the national standard B1 level. At the same time, it also improves the electrical insulation and arc resistance of the high-voltage cable. In order to improve the use effect of low-melting-point glass powder in ceramic flame-retardant polyolefin composite materials, preferably, the melting temperature of the low-melting-point glass powder is 350℃-550℃, and the average particle size is not more than 10μm. The melting temperature of the low-melting-point glass powder selected in the embodiment of the present invention is 350℃, and it is sieved through 2000 mesh.

[0072] Aminosilane coated wollastonite uses aminopropyl triethoxysilane to modify the surface of wollastonite (selected from Jiangxi Kete fine 400 mesh needle-shaped wollastonite powder), with a coating rate of ≥70%, which improves the bonding force between wollastonite and other components, thereby ensuring that the ceramic flame-retardant polyolefin composite material can achieve the mechanical strength and combustion performance required by the present invention. The addition of phlogopite powder can form a whole with the outer protective layer 9 during the combustion process, forming a drip-free ceramic body, and improving the fire retardant performance.

[0073] Preferably, the lithium borate salt is composed of lithium tetraborate, lithium metaborate and zinc borate in a mass ratio of 1:2:4. The use of the lithium borate salt in this combination can not only reduce the ceramic transition temperature of the ceramic flame retardant polyolefin composite material and improve the processing performance, but also significantly improve the mechanical strength and flame retardancy of the ceramic flame retardant polyolefin composite material.

[0074] Preferably, the halogen-free flame retardant is composed of nano magnesium hydroxide, magnesium stearate and silicone oil in a mass ratio of (0.2-0.5): 1: 1. The use of this combination of halogen-free flame retardants not only has excellent flame retardancy, but also ensures that the ceramic flame retardant polyolefin composite material has excellent mechanical strength and processing properties. The halogen-free flame retardant selected in the embodiment of the present invention is a mixture of nano magnesium hydroxide, magnesium stearate and silicone oil in a mass ratio of 1: 2: 2.

[0075] Preferably, the second silane coupling agent is composed of vinyl trimethoxy silane and aminopropyl triethoxy silane in a mass ratio of 3: 2. The combined silane coupling agent increases the crosslinking density between polyolefin resins and improves the mechanical properties, water resistance and high temperature resistance of the ceramic flame retardant polyolefin composite material.

[0076] Preferably, the outer shielding layer 8 is an aluminum foil Mylar tape, which provides double protection with the inner shielding layer 6, further improving the anti-interference, radiation resistance and other properties of the cable of the present invention, while improving the high temperature resistance and fire retardancy of the present invention.

[0077] Preferably, the outer protective layer 9 is a halogen-free, low-smoke, flame-retardant, and corrosion-resistant polyolefin mixture, which can withstand high temperatures of 150°C and low temperatures of -40°C, has an oxygen index ≥35, and has excellent mechanical properties, combustion performance, corrosion resistance, radiation resistance, and electrical insulation.

[0078] The halogen-free, low-smoke, flame-retardant and corrosion-resistant polyolefin mixture is composed of the following raw materials in parts by mass: 30-50 parts of linear low-density polyethylene, 10-15 parts of ultra-high molecular weight polyethylene, 25-40 parts of ethylene-ethyl acrylate copolymer, 15-30 parts of metallocene ethylene-octene copolymer, 15-30 parts of methyl vinyl silicone rubber, 20-40 parts of low-melting point glass powder, 15-25 parts of plasticizer, 30-50 parts of composite flame retardant, 10-15 parts of titanium aluminum oxide, 20-40 parts of filler, 0.3-0.5 parts of antioxidant, 0.2-0.4 parts of initiator DCP and 3-5 parts of third silane coupling agent.

[0079] In order to ensure that the present invention has excellent mechanical properties, combustion performance and corrosion resistance, the present invention preferably has a linear low-density polyethylene at 190°C, a melting index of 1.5 to 3 g / 10 min under a load of 2.16 kg (DFDA-7042 of Maoming Petrochemical is selected in the present embodiment); a molecular weight of ultra-high molecular weight polyethylene UHMWPE ≥ 4.5 million (GUR 4150 of Celanese, USA is selected in the present embodiment); a melting index of ethylene-ethyl acrylate copolymer at 190°C, a melting index of 5 to 10 g / 10 min under a load of 2.16 kg (AC 2618 of DuPont, USA is selected in the present embodiment); a melting index of metallocene ethylene-octene copolymer at 190°C, a melting index of 4 to 8 g / 10 min under a load of 2.16 kg (C5070D of SABIC is selected in the present embodiment). The performance and proportion setting of these components can ensure that the outer sheath of the present invention has excellent comprehensive performance and has better mechanical strength, flame retardancy and corrosion resistance.

[0080] The addition of methyl vinyl silicone rubber increases the crosslinking density of the polyolefin mixture, further improves the mechanical strength and toughness of the halogen-free, low-smoke, flame-retardant and corrosion-resistant polyolefin mixture, and also improves the water resistance and corrosion resistance of the polyolefin mixture. In the embodiment of the present invention, preferably, the vinyl-terminated methyl vinyl silicone rubber has a vinyl content of 0.21-0.24wt%, which is 110-3S from Nanjing Dongjue.

[0081] The addition of low melting point glass powder improves the mechanical strength, corrosion resistance, wear resistance, high temperature resistance and combustion performance of the halogen-free, low smoke, flame retardant and corrosion resistant polyolefin mixture. In the embodiment of the present invention, the low melting point glass powder is preferably selected from Hebei Jinghang, with a melting temperature of 350°C and sieved through 2000 mesh.

[0082] Preferably, the plasticizer is any one or two of trioctyl trimellitate, diisononyl phthalate, dipentaerythritol ester or ethylene glycol ester. The plasticizer has good compatibility with polyolefins, high plasticizing efficiency, low volatility, and good heat resistance, chemical corrosion resistance and electrical insulation, which improves the processing performance and flame retardancy of the halogen-free, low-smoke, flame-retardant and corrosion-resistant polyolefin mixture. In the embodiment of the present invention, the plasticizer is trioctyl trimellitate, which comes from Jinan Shengchen Chemical.

[0083] Preferably, the composite flame retardant is composed of the following raw materials in parts by mass: 40-60 parts of nano magnesium hydroxide, 30-40 parts of aluminum hydroxide and 10-20 parts of zinc borate. The composite flame retardant can ensure that the halogen-free, low-smoke, flame-retardant and corrosion-resistant polyolefin mixture has excellent low-smoke flame retardancy, can form a non-drip hard shell-like substance during the combustion process, and can also ensure that the halogen-free, low-smoke, flame-retardant and corrosion-resistant polyolefin mixture has excellent mechanical strength, corrosion resistance and processing properties. In the embodiment of the present invention, the formula of the composite flame retardant is: 50 parts of nano magnesium hydroxide (in the embodiment, it is selected from 5000 mesh nano magnesium hydroxide of Jiuzhuo Chemical), 35 parts of aluminum hydroxide (in the embodiment, it is selected from FR3801 of Zhongke Flame Retardant, with a particle size of 8000 mesh) and 15 parts of zinc borate (in the embodiment, it is selected from zinc borate HT-207 of Taixing New Materials).

[0084] Preferably, titanium aluminum oxide is a mixture of titanium dioxide and aluminum oxide in a mass ratio of 3:2, which can improve the corrosion resistance and aging resistance of the outer protective layer 9, and enable the outer protective layer 9 to achieve the mechanical strength, high temperature resistance, wear resistance and flame retardancy required by the present invention.

[0085] Preferably, the filler is composed of calcined kaolin (i.e., calcined kaolin YF-4000), phlogopite powder (calcined phlogopite powder selected from Deqian Mineral Products) and calcium carbonate (heavy calcium carbonate GS2500A selected from Korina New Materials) in a mass ratio of 1:2:1, which improves the mechanical strength, flame retardancy, corrosion resistance and wear resistance of the halogen-free, low-smoke, flame-retardant and corrosion-resistant polyolefin mixture.

[0086] Preferably, the antioxidant is antioxidant 1010, which improves the heat-oxidative aging resistance of the halogen-free, low-smoke, flame-retardant and corrosion-resistant polyolefin mixture, is not easy to migrate, and has high thermal stability.

[0087] Preferably, the third silane coupling agent is composed of vinyltrimethoxysilane and vinyltri(2-methoxyethoxy)silane in a mass ratio of 2:1, which increases the crosslinking density between polyolefin resins and improves the mechanical properties, water resistance and high temperature resistance of the halogen-free, low-smoke, flame-retardant and corrosion-resistant polyolefin mixture.

[0088] Preferably, a flame retardant and anti-corrosion polyurethane water-based paint is sprayed on the outer sheath 9 to form an outer protective coating, so that the outer sheath of the cable forms a double-layer protection, further improving the flame retardancy and corrosion resistance of the cable. The polyurethane water-based paint selected in the embodiment of the present invention is Akkad UR-36, which also has excellent waterproof, insulating, anti-aging and other properties.

[0089] The present invention also provides a method for preparing a corrosion-resistant and flame-retardant cross-linked polyolefin cable (hereinafter referred to as a single-core cable), which specifically comprises the following steps:

[0090] P1. The tinned copper wire is twisted by a cantilever single twisting machine to form a single conductor 1;

[0091] P2. Wrap the halogen-free and non-corrosive non-woven fabric around the conductor 1 to form an isolation layer 2;

[0092] P3. Wrap the low-smoke halogen-free flame-retardant cable material with an oxygen index greater than or equal to 40 on the outside of the isolation layer 2 to form an oxygen isolation layer 3;

[0093] P4. The high temperature 150 ℃ radiation cross-linked flame retardant polyolefin insulation material is extruded on the oxygen barrier layer 3 by an extruder to form an insulating layer 4;

[0094] P5. Wrap the halogen-free, low-smoke, high-flame-retardant tape made of non-woven fabric or glass fiber cloth around the insulating layer 4 to form a tape layer 5;

[0095] P6. The raw materials in the above-mentioned ferrite-containing polyolefin composite shielding material are weighed by mass, added into a high-speed mixer, mixed for 8-10 minutes at 480r / min and 110-120°C, cooled to below 50°C, and then conveyed to a twin-screw extruder for granulation to obtain a polyolefin composite shielding material; then, an extruder is used to extrude and coat the above-prepared polyolefin composite shielding material on the tape layer 5 at a temperature of 130-150°C to form an inner shielding layer 6;

[0096] P7. The raw materials in the ceramic flame-retardant polyolefin composite material are weighed by mass, added into a high-speed mixer, mixed for 10-15 minutes at 480r / min and 100-110°C, cooled to below 70°C, and then transported to a twin-screw extruder for granulation to obtain a ceramic flame-retardant polyolefin composite material; then, an extruder is used to extrude and coat the ceramic flame-retardant polyolefin composite material obtained above on the inner shielding layer 6 at a temperature of 125-135°C to form a flame-retardant layer 7;

[0097] P8. Wrap the aluminum foil Mylar tape around the flame retardant layer 7 to form an outer shielding layer 8;

[0098] P9. The above-mentioned halogen-free, low-smoke, flame-retardant, and corrosion-resistant polyolefin mixture is weighed by mass, added into a high-speed mixer, mixed for 8-10 minutes at 480r / min and 110-120°C, cooled to below 70°C, and then conveyed to a twin-screw extruder for granulation to obtain a halogen-free, low-smoke, flame-retardant, and corrosion-resistant polyolefin mixture; then, an extruder is used to extrude and coat the above-prepared halogen-free, low-smoke, flame-retardant, and corrosion-resistant polyolefin mixture on the outer shielding layer 8 at a temperature of 120-140°C to form an outer protective layer 9;

[0099] P10. Spray 2-4 layers of flame-retardant and anti-corrosion polyurethane water-based paint on the outer surface of the outer protective layer 9 to form a protective coating 10.

[0100] The corrosion-resistant and flame-retardant cross-linked polyolefin cable of the present invention is described below with reference to specific embodiments.

[0101] Inner shielding layer 6: polyolefin composite shielding material containing ferrite

[0102] Example 1

[0103] The ferrite-containing polyolefin composite shielding material is composed of the following raw materials in parts by mass: 50 parts of polypropylene resin, 32 parts of ethylene-vinyl acetate copolymer, 18 parts of ethylene-butyl acrylate copolymer, 8 parts of PP grafted maleic anhydride, 10 parts of carbon black, 5 parts of barium ferrite, 15 parts of flame retardant, 0.4 parts of initiator DCP, 1.5 parts of first silane coupling agent, 0.4 parts of antioxidant 1010, and 1.5 parts of lubricant CYD-P214.

[0104] The raw materials, raw material models and preparation process of the ferrite-containing polyolefin composite shielding material are all described in the above specific embodiments, and please refer to the above description for details. In addition, the barium ferrite in Example 1 is selected from the commercially available Wuhan Langbowan Biomedicine Company.

[0105] After testing, the tensile strength of Example 1 is 23.4 MPa, the elongation at break is 378.5%, the volume resistivity at 20°C is 6.8Ω·cm, the volume resistivity at 90°C is 20.4Ω·cm, and the melt index is 6.8 g / 10 min.

[0106] Example 2

[0107] The raw materials, components and preparation process of the ferrite-containing polyolefin composite shielding material of Example 2 are the same as those of Example 1, and specific reference is made to Example 1. The difference is that the barium ferrite of Example 2 is homemade, and the specific preparation method please refer to the description in the above specific implementation manner.

[0108] After testing, the tensile strength of Example 2 is 26.9 MPa, the elongation at break is 425.6%, the volume resistivity at 20°C is 4.3Ω·cm, the volume resistivity at 90°C is 12.5Ω·cm, and the melt index is 8.2 g / 10 min.

[0109] Comparative Example 1

[0110] The preparation method of the polyolefin composite shielding material of Comparative Example 1 is the same as that of Example 2, with specific reference to Example 1, except that barium ferrite is not added in Comparative Example 1, and the amount of carbon black added is 15 parts.

[0111] After testing, the tensile strength of Comparative Example 1 is 21.6 MPa, the elongation at break is 327.5%, the volume resistivity at 20°C is 15.3Ω·cm, the volume resistivity at 90°C is 42.8Ω·cm, and the melt index is 5.6 g / 10 min.

[0112] Comparative Example 2

[0113] The preparation method of the polyolefin composite shielding material of Comparative Example 2 is the same as that of Example 2, specifically referring to Example 1, except that barium ferrite is not added in Comparative Example 2, and the amount of carbon black added is 25 parts.

[0114] After testing, the tensile strength of Comparative Example 2 was 12.8 MPa, the elongation at break was 185.4%, the volume resistivity at 20°C was 9.5Ω·cm, the volume resistivity at 90°C was 25.8Ω·cm, and the melt index was 4.5 g / 10 min.

[0115] Comparative Example 3

[0116] The polyolefin composite shielding material of Comparative Example 3 is prepared in the same manner as in Example 2, specifically referring to Example 1, except that the flame retardant in Comparative Example 3 is composed of microencapsulated red phosphorus and magnesium hydroxide in a mass ratio of 1:9.

[0117] After testing, the tensile strength of Comparative Example 3 is 22.5 MPa, the elongation at break is 368.5%, the volume resistivity at 20°C is 5.2Ω·cm, the volume resistivity at 90°C is 15.9Ω·cm, and the melt index is 6.5 g / 10 min.

[0118] Flame retardant layer 7: ceramic flame retardant polyolefin composite material

[0119] Example 3

[0120] The ceramic flame-retardant polyolefin composite material is composed of the following raw materials in parts by mass: 38 parts of low-density polyethylene, 25 parts of ethylene-methyl acrylate copolymer, 37 parts of ethylene propylene diene terpolymer, 40 parts of aminosilane-coated wollastonite, 16 parts of low-melting-point glass powder, 18 parts of phlogopite powder, 8 parts of lithium borate salt, 0.3 parts of initiator DCP, 10 parts of halogen-free flame retardant and 1.8 parts of a second silane coupling agent.

[0121] The raw materials, raw material models, and preparation process of the ceramic flame-retardant polyolefin composite material are all described in the above specific implementation manner. Please refer to the above description for details.

[0122] Comparative Example 4

[0123] The ceramic flame-retardant polyolefin composite material of Comparative Example 4 is prepared in the same manner as in Example 3, with specific reference to Example 3, except that the wollastonite in Comparative Example 4 is not coated with aminosilane, that is, fine 400-mesh needle-shaped wollastonite powder from Jiangxi Kete is directly added.

[0124] Comparative Example 5

[0125] The ceramic flame-retardant polyolefin composite material of Comparative Example 5 is prepared in the same manner as in Example 3, with specific reference to Example 3, except that no phlogopite mica powder is added in Comparative Example 6, and the amount of low-melting-point glass powder added is 34 parts.

[0126] Comparative Example 6

[0127] The ceramic flame-retardant polyolefin composite material of Comparative Example 6 is prepared in the same manner as in Example 3, with specific reference to Example 3, except that zinc borate is not added in Comparative Example 5, and the mass ratio of lithium tetraborate to lithium metaborate is 1:2.

[0128] The ceramic flame-retardant polyolefin composite materials prepared in the above Example 3 and Comparative Examples 4-6 were made into test specimens for performance testing, as shown in Table 1 below.

[0129] Table 1 Performance test results of ceramic flame retardant polyolefin composites

[0130]

[0131]

[0132] It can be seen from the experimental results in Table 1 above that the ceramic flame-retardant polyolefin composite material of the present invention has high mechanical strength, chemical stability and flame retardancy, and can be used for a long time at 150°C.

[0133] Outer sheath 9: Halogen-free, low-smoke, flame-retardant, corrosion-resistant polyolefin mixture

[0134] Example 4

[0135] The halogen-free, low-smoke, flame-retardant and corrosion-resistant polyolefin mixture is composed of the following raw materials in parts by mass: 40 parts of linear low-density polyethylene, 12 parts of ultra-high molecular weight polyethylene, 30 parts of ethylene-ethyl acrylate copolymer, 18 parts of metallocene ethylene-octene copolymer, 22 parts of methyl vinyl silicone rubber, 32 parts of low-melting point glass powder, 20 parts of plasticizer, 36 parts of composite flame retardant, 12 parts of titanium aluminum oxide, 35 parts of filler, 0.4 parts of antioxidant 1010, 0.3 parts of initiator DCP and 3.6 parts of third silane coupling agent.

[0136] The raw materials, raw material models, and preparation process of the halogen-free, low-smoke, flame-retardant, and corrosion-resistant polyolefin mixture are all specified in the above specific implementation manner. Please refer to the above description for details.

[0137] Comparative Example 7

[0138] The halogen-free, low-smoke, flame-retardant, and corrosion-resistant polyolefin mixture of Comparative Example 7 is prepared in the same manner as in Example 4, with specific reference to Example 4, except that methyl vinyl silicone rubber is not added in Comparative Example 7, but 22 parts of hydrogenated nitrile rubber are added.

[0139] Comparative Example 8

[0140] The halogen-free, low-smoke, flame-retardant, and corrosion-resistant polyolefin mixture of Comparative Example 8 is prepared in the same manner as in Example 4, with specific reference to Example 4, except that titanium aluminum oxide is not added in Comparative Example 8, but 12 parts of iron tin oxide are added, and the iron tin oxide is a mixture of iron oxide and tin oxide in a mass ratio of 2:1.

[0141] Comparative Example 9

[0142] The halogen-free, low-smoke, flame-retardant, and corrosion-resistant polyolefin mixture of Comparative Example 9 is prepared in the same manner as in Example 4, with specific reference to Example 4. The difference is that the composite flame retardant in Comparative Example 9 is composed of 50 parts of nano-magnesium hydroxide, 35 parts of aluminum hydroxide, and 15 parts of carbonizing agent CFA (selected from triazine carbonizing agent CFA of Xijia Chemical).

[0143] The halogen-free, low-smoke, flame-retardant, and corrosion-resistant polyolefin mixtures prepared in the above Example 4 and Comparative Examples 7-9 were made into samples for performance testing, as shown in Table 2 below.

[0144] Table 2 Performance test results of halogen-free, low-smoke, flame-retardant and corrosion-resistant polyolefin mixtures

[0145]

[0146]

[0147] It can be seen from the experimental results in Table 2 above that the halogen-free, low-smoke, flame-retardant and corrosion-resistant polyolefin mixture of the present invention can withstand high and low temperatures and has high mechanical strength, combustion performance, corrosion resistance, radiation resistance and electrical insulation.

[0148] Application Example 1

[0149] The preparation method in the above specific embodiment is used to make a corrosion-resistant and flame-retardant cross-linked polyolefin cable. The raw materials and structure are as described in the specific embodiment, and the cable core is a wire core, the conductor 1 is a conductor, the diameter is 18.00mm, the thickness of the isolation layer 2 is 0.2mm, the thickness of the insulation layer 4 is 2.2mm, the thickness of the oxygen barrier layer 3 is 2.1mm, the thickness of the tape layer 5 is 0.2mm, the thickness of the inner shielding layer 6 is 0.5mm, the thickness of the flame retardant layer 7 is 1.5mm, the thickness of the outer shielding layer 8 is 0.3mm, the thickness of the outer sheath 9 is 2.5mm, and the protective coating 10 is 0.02mm. Among them, the preparation methods of the ferrite-containing polyolefin composite shielding material, the ceramic flame-retardant polyolefin composite material and the halogen-free low-smoke flame-retardant and corrosion-resistant polyolefin mixture refer to Example 1, Example 3 and Example 4 respectively.

[0150] Application Example 2

[0151] The preparation method in the above specific embodiment is used to make a corrosion-resistant and flame-retardant cross-linked polyolefin cable. The raw materials and structure are as described in the specific embodiment, and the cable core is a wire core, the conductor 1 is 1, the diameter is 18.00mm, the thickness of the isolation layer 2 is 0.2mm, the thickness of the insulation layer 4 is 2.2mm, the thickness of the oxygen barrier layer 3 is 2.1mm, the thickness of the tape layer 5 is 0.2mm, the thickness of the inner shielding layer 6 is 0.5mm, the thickness of the flame retardant layer 7 is 1.5mm, the thickness of the outer shielding layer 8 is 0.3mm, the thickness of the outer sheath 9 is 2.5mm, and the protective coating 10 is 0.02mm. Among them, the preparation methods of the ferrite-containing polyolefin composite shielding material, the ceramic flame-retardant polyolefin composite material and the halogen-free low-smoke flame-retardant and corrosion-resistant polyolefin mixture refer to Example 2, Example 3 and Example 4 respectively. It is worth noting that the thickness difference of each layer in Application Example 1 and Application Example 2 is within a reasonable range.

[0152] The performance of the corrosion-resistant and flame-retardant cross-linked polyolefin cable produced in the above Application Example 1-2 was tested, and the test results are shown in Table 3.

[0153] Table 3 Cable performance test results

[0154]

[0155] It can be seen from Application Examples 1-2 that the corrosion-resistant and flame-retardant cross-linked polyolefin cable and its production method of the present invention start from the perspective of optimizing the formulation of various cable components and the inner shielding layer 6, the flame-retardant outer sheath, etc., and fully utilize the synergistic effect between the various components and components to overcome the shortcomings described in the background technology, ensuring that the combustion performance of the cable of the present invention reaches flame retardant Class A and the combustion performance level reaches Class B1. The product has a simple structure, is easy to manufacture, has a wide range of applications, and is low in cost. It has the characteristics of excellent flame retardancy, excellent electrical properties, good mechanical properties, and strong corrosion resistance.

[0156] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0157] The above embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention.

Claims

1. A corrosion-resistant and flame-retardant cross-linked polyolefin cable, comprising a cable core, a tape layer (5), an inner shielding layer (6), a flame-retardant layer (7), an outer shielding layer (8), an outer sheath (9) and a protective coating (10), wherein the cable core is one or more wire cores, wherein the wire core is a conductor (1), a separation layer (2), an insulating layer (4) and an oxygen barrier layer (3), characterized in that: The conductor (1) is wrapped with an isolation layer (2), the isolation layer (2) is extruded with an oxygen-isolating layer (3), and the oxygen-isolating layer (3) is extruded with an insulating layer (4); The insulating layer (4) is wrapped with a tape layer (5), the tape layer (5) is extruded with an inner shielding layer (6), the inner shielding layer (6) is extruded with a flame retardant layer (7), the flame retardant layer (7) is wrapped with an aluminum foil Mylar tape to form an outer shielding layer (8), the outer shielding layer (8) is covered with an outer protective layer (9), and the outer protective layer (9) is coated with a protective coating (10); The inner shielding layer (6) is a polyolefin composite shielding material containing ferrite; The flame retardant layer (7) is a ceramic flame retardant polyolefin composite material; The outer protective layer (9) is a halogen-free, low-smoke, flame-retardant, and corrosion-resistant polyolefin mixture.

2. The corrosion-resistant and flame-retardant cross-linked polyolefin cable according to claim 1, characterized in that: The polyolefin composite shielding material is composed of the following raw materials in parts by mass: 40-60 parts of polypropylene resin, 25-35 parts of ethylene-vinyl acetate copolymer, Ethylene-butyl acrylic acid copolymer 15-25 parts, PP grafted maleic anhydride 5-10 parts, Carbon black 5-15 parts, 3-6 parts of barium ferrite, Flame retardant 10-20 parts, The first silane coupling agent 0.5-2 parts, Initiator DCP 0.1-0.5 parts, Antioxidant 0.3-0.5 parts, 1-3 parts of lubricant.

3. The corrosion-resistant and flame-retardant cross-linked polyolefin cable according to claim 2, characterized in that: The preparation method of the barium ferrite is: S1. Add appropriate proportions of ferrous nitrate, ferric nitrate and polyethylene glycol to an appropriate amount of deionized water and stir continuously until dissolved, then add ammonia water to adjust the pH value to 10-11, heat to 50-70 ° C for 2-4h, filter, wash and dry to obtain an iron oxide precursor; S2. The iron oxide precursor and barium carbonate prepared above are added to glacial acetic acid and stirred until dissolved to form a mixed solution; S3. Add an appropriate amount of dilute nitric acid to the mixed solution, stir for 5-10 minutes, then heat to 200-220°C to react for 3-5 hours, cool to room temperature, filter, and then wash with deionized water and anhydrous ethanol 2-3 times in succession, and vacuum dry at 80°C for 2-5 hours to obtain barium ferrite.

4. The corrosion-resistant and flame-retardant cross-linked polyolefin cable according to claim 3, characterized in that: The molar ratio of ferrous nitrate to ferric nitrate is (0.4-0.6):1; The molar ratio of iron to barium carbonate in the iron oxide precursor is (9-10):

1.

5. The corrosion-resistant and flame-retardant cross-linked polyolefin cable according to claim 1, characterized in that: The ceramic flame-retardant polyolefin composite material is composed of the following raw materials in parts by weight: 30-50 parts of low-density polyethylene, 15-30 parts of ethylene-methyl acrylate copolymer, 25-40 parts of ethylene propylene diene terpolymer, 30-50 parts of aminosilane-coated wollastonite, 10-20 parts of low-melting-point glass powder, 15-25 parts of phlogopite powder, 5-10 parts of lithium borate salt, 6-12 parts of halogen-free flame retardant, 0.2-0.4 parts of initiator DCP and 1-3 parts of second silane coupling agent.

6. The corrosion-resistant and flame-retardant cross-linked polyolefin cable according to claim 5, characterized in that: The aminosilane-coated wollastonite uses aminopropyltriethoxysilane to perform surface modification on the wollastonite, with a coating rate of ≥70%; The lithium borate salt is composed of lithium tetraborate, lithium metaborate and zinc borate in a mass ratio of 1:2:4; The halogen-free flame retardant is composed of nano magnesium hydroxide, magnesium stearate and silicone oil in a mass ratio of (0.2-0.5):1:1; The second silane coupling agent consists of vinyltrimethoxysilane and aminopropyltriethoxysilane.

7. The corrosion-resistant and flame-retardant cross-linked polyolefin cable according to claim 1, characterized in that: The halogen-free, low-smoke, flame-retardant and corrosion-resistant polyolefin mixture is composed of the following raw materials in parts by weight: Linear low-density polyethylene 30-50 parts, Ultra-high molecular weight polyethylene 10-15 parts, 30-50 parts of ethylene-ethyl acrylate copolymer, 15-30 parts of metallocene ethylene-octene copolymer, 15-30 parts of methyl vinyl silicone rubber, 20-40 parts of low melting point glass powder, Plasticizer 15-25 parts, 30-50 parts of composite flame retardant, 10-15 parts of titanium aluminum oxide, 20-40 parts of filler, Antioxidant 0.3-0.5 parts, Initiator DCP 0.2-0.4 parts, 3-5 parts of the third silane coupling agent.

8. The corrosion-resistant and flame-retardant cross-linked polyolefin cable according to claim 7, characterized in that: The composite flame retardant is composed of the following raw materials in parts by mass: 40-60 parts of nano magnesium hydroxide, 30-40 parts of aluminum hydroxide and 10-20 parts of zinc borate.

9. The corrosion-resistant and flame-retardant cross-linked polyolefin cable according to claim 7, characterized in that: The titanium aluminum oxide is a mixture of titanium dioxide and aluminum oxide in a mass ratio of 3:2; The filler is composed of calcined kaolin, phlogopite powder and calcium carbonate in a mass ratio of 1:2:1; The third silane coupling agent is vinyltrimethoxysilane.

10. The corrosion-resistant and flame-retardant cross-linked polyolefin cable according to claim 1, characterized in that: The isolation layer (2) is a halogen-free, non-corrosive non-woven fabric made of polyester fiber or terylene fiber; The insulating layer (4) is a 150°C high temperature resistant radiation cross-linked flame retardant polyolefin insulating material; The oxygen barrier layer (3) is a low-smoke, halogen-free, flame-retardant cable material with an oxygen index greater than or equal to 40; The wrapping tape layer (5) is a halogen-free, low-smoke, high-flame-retardant tape made of non-woven fabric or glass fiber fabric, and is wrapped around the insulating layer (4) in an overlapping manner, with an overlap rate of 15-20%; The outer shielding layer (8) is an aluminum foil Mylar tape; The protective coating (10) is a flame-retardant and corrosion-resistant polyurethane water-based coating.

Citation Information

Patent Citations

  • High-voltage soft polyolefin wire material for new energy automobile and preparation method thereof

    CN110903589A

  • Anti-interference high-flame-retardant environment-friendly transponder data transmission cable

    CN111029031A

  • Medium-high voltage cable for smart power grid and preparation method thereof

    CN116913587A

  • Ethylene propylene rubber insulated cold-resistant flame-retardant first-level direct-current flexible cable and manufacturing method thereof

    CN113571240A

  • Flame-retardant, wear-resistant, anti-torsion and anti-electromagnetic interference cable for robot body and production method

    CN113871092A

Cited By

  • Flexible string group photovoltaic cable and preparation method thereof

    CN120183782A

  • Flexible string group photovoltaic cable and its preparation method

    CN120183782B

  • High-flame-retardant corrosion-resistant medium-voltage cross-linked polyethylene insulated power cable

    CN120280218A

  • Corrosion-resistant anti-dripping fire-resistant cable and preparation method thereof

    CN121034741A

  • Fireproof variable frequency cable

    CN121394043A